The Essential Entrepreneur : What It Takes to Start, Scale, and Sell a Successful Business - Turner, Richard (John Wiley & Sons, Incorporated, 2023)
A toolkit for entrepreneurial success In The Essential Entrepreneur, celebrated entrepreneur and business strategist Richard Turner delivers a practical, step-by-step approach to starting and growing a thriving enterprise. If you're ready to take your fledgling business to the next level--and finally follow that brilliant big idea--this guide covers everything you'll need to navigate the challenges ahead. Richard shares straightforward advice and hands-on, real-world lessons outlining the key points you need to know to start and grow your venture. And his lessons are supported by the experience and wisdom of a panel of diverse experts: Tobi Pearce (co-founder of SWEAT), Flavia Tata Nardini (of Fleet Space), Simon Haigh (of Haigh's Chocolates), and Kirsten Bernhardt (skilled investment manager). You'll discover how to: Make a splash in your industry by taking advantage of market weaknesses, disrupting the status quo and creating new openings Sort the good ideas from the bad: validate your business (whether it's a product or a service) and maximise its value Position your brand so that what you do is clear and instantly recognisable Create a business plan that really works, factoring in timing, going to market, managing finance, managing growth and more Understand the logistics of a successful and profitable operation, from sourcing suppliers to production, warehousing and distribution Most small businesses struggle to get moving. This is the book that will help you get ahead in the race. A can't-miss resource for start-up entrepreneurs and business owners, The Essential Entrepreneur outlines everything you need to know to hit the ground running.